Antifungal activity of oxidative damaging agents in combination with metal cations against Trichophyton rubrum isolated from a dermatological patient - Thi Nguyet, Nguyen; Cam Van, Tran; Xuan Thu, Nguyen; Thi Mai Phuong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Trichophyton rubrum is a causative agent responsible for human chronic dermatophytosis worlwide. It is a common causative agent of the dermatophyte infections and resistant to many antifungal drugs. Oxidative damaging agents belong to a strong antimicrobial group and have been intensively investigated. The synergistic oxidative damage can occur if the agents react with metal cations. Therefore, in this study the antifungal activity of formulas containing the two oxidative damaging agents, including hydrogen peroxide (H2O2) and 8-hydroxyquinoline (8HQ), in combination with metal cations has been determined to examine the synergistic damage in T. rubrum isolated from the skin of a dermatological patient. The isolate was identified by morphology observations, biochemical tests and sequence analysis of ITS1-4 gene, in comparison with the similar ITS nucleotide sequences of others. The obtained results showed that the isolated fungal strain had physiological and biochemical characteristics of T. rubrum with more than 99% identity of the T. rubrum CBS 392.58 ITS sequence with OL347577 accession numbers. The antifungal tests indicated that the combinations of 2 mM Cu2+ + 0.05% H2O2; 2 mM Cu2++ 0.005% 8HQ; 2 mM Cu2+ + 0.005% 8HQ + 0.05% H2O2 exerted the best antifungal activity against the isolated T. rubrum with the diameter of inhibition zones of 22, 25 and 28 mm, respectively. Among the combinations containing Zn2+, the only formula of 2 mM Zn2+ + 0.05% H2O2 exhibited the desired effect, while the combinations containing Fe2+ did not show any activity. Thus, our study suggested a potential use of Cu2+ + 0.05% H2O2; 2 mM Cu2++ 0.005% 8HQ and 2 mM Cu2+ + 0.005% 8HQ + 0.05% H2O2 formulas as new potential antifungal agents against T. rubrum due to their synergistic oxidative damage.